Study on Pattern of Lip Prints and its Relation to Sex and Blood Groups in Telangana Population (Medico Legal Update, 2020)
A cross sectional study on the pattern of lip prints was conducted among the population of Telangana region.A sample of 140 individuals comprising of 70 males and 70 females were taken from both medical andnursing students of the Mediciti Institute of Medical Sciences, Medchal, Telangana.The present study showed type-1 (vertical groove running across the lip) is the most common pattern presentin all the quadrants of the lip in both males and females. In the left upper quadrant, it is found to be 51.4%,followed by 37.1% in the left upper right quadrant, 49.3% in the lower left quadrant and 53.6% in the lowerright quadrant. Type-2 pattern (vertical partial length groove) is the second common pattern, in the upperleft quadrant, it is 37.1%, in the upper right 42.1%, in the lower-left 34.3% and lower right quadrant 27.9%.Type-3 (Branched groove) observed as the third common pattern in the study population, in the upper leftquadrant it is 11.4%, upper right 18.6%, lower left 15.7%, lower right quadrant 17.9%. Type-5 (Reticularpattern) is noticed in the upper right quadrant in 1.4%, lower left 0.7%, lower right 0.7% and not found inthe upper left quadrant. The type-6 pattern is found upper right quadrant in 0.7% of study population andType-4 pattern (intersected groove) is not found in our study group.Our study revealed that the pattern of lip prints for each individual in each quadrant is unique. Accordingto our study, there is no sex difference with lip print patterns. Study also revealed that there is no relationbetween lip print patterns and the blood groups, a near significant relation observed with the chi-square testin one quadrant, but not considered as significant.Lip print patterns are constant, do not change with time and the uniqueness of its nature in each individual,it can be used for personal identification in various medico-legal issues